Taxonomy of Miocene Bryozoans from As Sahabi area, Ajdabiyah Trough, NE Sirt Basin, Libya 1 - Muftah, Ahmed; El-Safori , Yasser (Libyan Journal of Science &Technology, 2022)
The exposed Pre-Sahabi rock unit formation "M" at As Sahabi area in Sirt Basin is analyzed micro paleontologically for bryozoans. Fourteen species belonging to eleven genera of bryozoan have been identified, described for the first time. In addition, the importance of the present study is to determine the paleo environmental occurrences as is performed herein with particular attention to their paleo geographical distribution. A comparison with the coeval sites from Siwa Oasis, the Cairo-Suez Road section in Egypt, as well as the Maradah Formation from Sirt Basin in Libya, has been revealed some similarities between these sites.